Korelasi Hasil Pemeriksaan Laboratorium dan Diagnostik pada Pasien Diabetes Mellitus - Supriyadi Supriyadi; Novita Dewi (Universitas Baiturrahim, 2022)
Diabetes Mellitus (DM) is a serious obstacle in health causing death, disease severity, due to the process of oxidative reactions producing free radicals that damage tissues, which are complications of the disease. Complications are micro and macrovascular in the liver and heart which are characterized by increased results of laboratory and diagnostic tests in DM patients during the pandemic. The purpose of the study was to determine the correlation between laboratory and diagnostic results in DM patients. The research method uses a correlation design with a cross-sectional approach using secondary data in the form of medical records from March-December 2020, a sample of 25 DM patients who underwent SGOT, SGPT, LDL, and ECG tests were statistically tested with chi-square. The results showed that there was no correlation with laboratory results (LDL, EKG) At most 56% fasting blood sugar was abnormal with abnormal LDL, there was no correlation between laboratory and diagnostic results (LDL) in DM patients with p value = (0.2). There is no correlation between laboratory and diagnostic results (ECG) in DM patients with p value = (0.54). At most 52% fasting blood sugar was abnormal with abnormal ECG, no correlation of laboratory and diagnostic results (ECG) in DM patients with p value = (1,0)